Measuring the relationship between spatial configuration concept variables and flexibility components - Hessari, Pedram; Chegeni, Farhad (Journal of Architecture and Urbanism, 2022)
Flexibility has been one of the valuable concepts in architecture due to the emphasis on the formation of a variable space to meet the needs of users and their peace and comfort over time. The main components of flexibility in a space system are multi-functional space, seasonal and daily displacement, and component separation and aggregation. Overall flexibility is a structural and conceptual concept that means the ability to make internal changes in a spatial system. On the other hand, the concept of spatial configuration emphasizes that space is the main factor and core of how events occur. To understand and explain the spatial configuration, one should look for a suitable method that responds to the environmental characteristics, one of the most important methods for understanding the spatial configuration is the space arrangement method. This method determines the configuration of a spatial system with the help of its variables, which are: coherence, depth, space difference, isovist, and visual accessibility. The main goal of this research is to know the relationship between spatial configuration variables and flexibility components in the spatial system of traditional houses in the Sufian neighborhood of Borujerd. This research is of applied type and has been done through correlation strategy and space layout method. The tool for collecting information in this research is documentary and library research and a survey through a questionnaire. To evaluate the variables and components of spatial configuration and flexibility, the relationship between the components and variables is first measured using the correlation method and spss software. The statistical population for measuring the relationship between flexibility components and spatial configuration variables is 25 experts and university professors. In the next step, five houses from the traditional houses of the Sufian Boroujerd neighborhood will be measured and evaluated using specialized space layout software to determine the variables of the concept of spatial configuration and their relationship with flexibility components. The results of this research show that the multi-functional space component in flexibility with depth and visual accessibility variables in the concept of spatial configuration, the seasonal and daily displacement component in flexibility with interconnected variables, space difference and isovist in the concept of spatial configuration and the component of separation and aggregation in flexibility is related to the interlinking variables, depth, and difference of space in the concept of spatial configuration.